Effects of a community-level intervention on maternal health care utilization in a resource-poor setting of Northern Ghana - Alex Bapula Kassim; Sam Kofi Newton; William Dormechele; Beatrice Baah Rahinatu; Clement Tiimim Yanbom; Isaac Kofi Yankson; Easmon Otupiri (BMC, 2023)
Abstract Background This study aimed to assess the effects of health education and community-level participatory interventions at the community level and the use of community maternal health promoters on the utilization of maternal health care services in poor rural settings of northern Ghana. Methods A randomized controlled survey design was conducted from June 2019 to July 2020 in two rural districts of northern Ghana. A multistage cluster sampling technique was used to select the participants. Data were collected from a repeated cross-sectional household survey. Descriptive analysis, bivariate and covariates adjusted simple logistic regression analyses were performed using STATA version 16 statistical software. Results At post-intervention, the two groups differed significantly in terms of ANC (p = 0.001), skilled delivery (SD) (p = 0.003), and PNC (p < 0.0001). Women who received health education on obstetric danger signs had improved knowledge by 50% at the end of the study. Women who received the health education intervention (HEI) on practices related to ANC and skilled delivery had increased odds to utilize ANC (AOR = 4.18; 95% CI = 2.48-7.04) and SD (AOR = 3.90; 95% CI = 1.83-8.29) services. Institutional delivery and PNC attendance for at least four times significantly increased from 88.5 to 97.5% (p < 0.0001), and 77.3-96.7% (p < 0.0001) respectively at postintervention. Women who had received the HEI were significantly more likely to have good knowledge about obstetric danger signs (AOR = 10.17; 95% CI = 6.59-15.69), and BPCR (AOR = 2.10; 95% CI = 1.36-3.24). Women who had obtained tertiary education were significantly more likely to make at least four visits to ANC (AOR = 2.38; 95% CI = 0.09-1.67). Conclusions This study suggests that the use of health education and participatory sessions led by community-based facilitators could be a potentially effective intervention to improve the knowledge of women about obstetric danger signs and encourage the uptake of maternity care services in resource-poor settings of Ghana.